Quantitative determination of 12-hydroxyeicosatetraenoic acids by chiral liquid chromatography tandem mass spectrometry in a murine atopic dermatitis model - Hong, Seong-Ho; Han, Ji Eun; Ko, Ji-Seung; Do, Sun Hee; Lee, Eung Ho; Cho, Myung-Haing (Journal of veterinary science (Suwŏn-si, Korea), 2015)
Atopic dermatitis, one of the most important skin diseases, is characterized by both skin barrier impairment and immunological abnormalities. Although several studies have demonstrated the significant relationship between atopic dermatitis and immunological abnormalities, the role of hydroxyeicosatetraenoic acids (HETE) in atopic dermatitis remains unknown. To develop chiral methods for characterization of 12-HETE enantiomers in a 1-chloro-2,4-dinitrochlorobenzene (DNCB)-induced atopic dermatitis mouse model and evaluate the effects of 12-HETE on atopic dermatitis, BALB/c mice were treated with either DNCB or acetone/olive oil (AOO) to induce atopic dermatitis, after which 12(R)- and 12(S)-HETEs in the plasma, skin, spleen, and lymph nodes were quantified by chiral liquid chromatography-tandem mass spectrometry. 12(R)- and 12(S)-HETEs in biological samples of DNCB-induced atopic dermatitis mice increased significantly compared with the AOO group, reflecting the involvement of 12(R)- and 12(S)-HETEs in atopic dermatitis. These findings indicate that 12(R)- and 12(S)-HETEs could be a useful guide for understanding the pathogenesis of atopic dermatitis.